3D printed hydrogel/PCL core/shell fiber scaffolds with NIR-triggered drug release for cancer therapy and wound healing. (1st September 2021) - Liu, Chunyang; Wang, Zhiyong; Wei, Xiaoyue; Chen, Birui; Luo, Yongxiang
Abstract: Hydrogel based scaffolds with the ability of on-demand drug delivery gained increasing interests for localized cancer therapy and tissue engineering application. However, most drug-loaded hydrogels are generally not suitable for long-term drug delivery, because of the uncontrolled diffusion of drugs from the swollen hydrogels. Therefore, in this study, a core/shell fiber scaffold was fabricated by coating a homogeneous layer of polycaprolactone (PCL) on the 3D printed alginate-gelatin hydrogel scaffolds. The PCL coatings could reduce the free diffusion of drugs from the core gels. Subsequently, polydopamine (PDA) was coated on the Gel/PCL core/shell scaffolds, endowing the scaffolds with great photothermal effects. Thus, near-infrared (NIR) laser triggered on-demand drug release was realized in this system due to the thermally induced sol-gel transition of the core gels. The released drugs (doxorubicin) and photothermal therapy could effectively prohibit or ablate tumor in vitro and in vivo . Additionally, the Gel/PCL/PDA core/shell scaffold could serve as platform for promoting wound healing. Therefore, the reported Gel/PCL/PDA core/shell scaffolds have the potential for application in localized cancer therapy and tissue regeneration. Especially for those cancer patients suffering surgical resection, the scaffolds could be implanted in the resection site to kill the residual or recurrent cancer cells, as well as to repair the tissue defects caused by surgery. Statement of significance: This paper reported a facile strategy to realize stimuli-triggered on demand drug release in vitro and in vivo. Polycaprolactone (PCL) and polydopamine were sequentially deposited on the surface of 3D printed drug-loaded alginate/gelatin scaffold. PCL encapsulation could effectively reduce the free diffusion of drugs from the core hydrogel, achieving sustained drug release. Polydopamine with good photothermal effects endowed the scaffold with stimuli-triggered drug release in response to near-infrared (NIR) laser irradiation. This scaffold could be applied for localized cancer therapy and tissue regeneration. Especially for those cancer patients suffering surgical resection, the scaffolds could be implanted in the resection site to kill the residual or recurrent cancer cells, as well as to repair the tissue defects caused by surgery. Graphical abstract: Image, graphical abstract